2013
DOI: 10.1182/blood.v122.21.2090.2090
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Improvement In Clinical Outcomes With Bortezomib-Thalidomide-Dexamethasone Vs Thalidomide-Dexamethasone Incorporated Into Double Autologous Transplantation For Multiple Myeloma: An Updated Analysis Of Phase 3 Gimema-MMY-3006 Study

Abstract: Over the last years, incorporation of novel agents into autologous stem cell transplantation (ASCT) has improved markedly the outcomes of younger patients with newly diagnosed multiple myeloma (MM). Superior results with experimental treatments vs previous standards of care have been frequently reported after preliminary analyses and need to be confirmed with longer follow up. The randomized phase 3 GIMEMA-MMY-3006 study was designed to compare bortezomib-thalidomide-dexamethasone (VTD) vs thalidomide-dexameth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Our findings of high activity of VTD induction (Ludwig et al , ) that persists over the long term are consistent with results reported for the VTD regimen in the Gruppo Italiano Malattie Ematologiche dell'Adulto (GIMEMA) MMY‐3006 (Cavo et al , , , ) and Programa para el Estudio de la Terapéutica en Hemopatías Malignas/Grupo Español de MM (PETHEMA/GEM) phase III (Rosiñol et al , ,b) trials in newly diagnosed MM, and confirm VTD as one of the most clinically active regimens in this setting. This is supported by a recent meta‐analysis showing significant superiority of VTD over VCD, both in terms of activity and of tolerance (Leiba et al , ), and by a retrospective comparison of the VTD and VCD arms of large European trials (Cavo et al , ).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings of high activity of VTD induction (Ludwig et al , ) that persists over the long term are consistent with results reported for the VTD regimen in the Gruppo Italiano Malattie Ematologiche dell'Adulto (GIMEMA) MMY‐3006 (Cavo et al , , , ) and Programa para el Estudio de la Terapéutica en Hemopatías Malignas/Grupo Español de MM (PETHEMA/GEM) phase III (Rosiñol et al , ,b) trials in newly diagnosed MM, and confirm VTD as one of the most clinically active regimens in this setting. This is supported by a recent meta‐analysis showing significant superiority of VTD over VCD, both in terms of activity and of tolerance (Leiba et al , ), and by a retrospective comparison of the VTD and VCD arms of large European trials (Cavo et al , ).…”
Section: Discussionsupporting
confidence: 91%
“…One trial did not report HR data on OS . All selected RCT reported HR data on PFS, nine reported frequency of gastrointestinal AE, while eight reported data on CR and ORR, seven on hematological, infectious, and thrombotic AE and five on cardiac AE. Characteristics of the 10 selected RCT are shown in Table , and specifications of each therapeutic protocol are available in Table .…”
Section: Resultsmentioning
confidence: 99%
“…From these references, 21 published articles deriving from 10 different RCT, with a total of 6474 patients, were eventually considered eligible for inclusion in meta-analysis. 11,12,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] One trial did not report HR data on OS. 32 and five on cardiac [28][29][30][31][32][33][34][35][36]38,39,43 AE.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations